Acceptability of routine domestic abuse enquiry within sexual health services. (May 2022) - Platt, Elizabeth; Hepworth, Eleanor; Rayment, Michael; Melendez-Torres, G.J.; Duff, Fiona; Cohen, Charlotte
Background: Our sexual health services (SHS) introduced routine domestic abuse (DA) enquiry in April 2018 following targeted staff training. A survey was undertaken to ascertain attitudes towards the initiative. Methods: Between October 2019 and March 2020, patients were invited to respond to an anonymous questionnaire by SMS. Clinical staff were emailed a separate survey. Results: The patient response rate was 40% (226/562): 72% (161/226) female, 80% (179/226) heterosexual, 19% (42) LGBT, 47% (106) aged 25-34 and 25% (57) aged 18-24. Almost all (97%, 220) recalled routine enquiry at their clinic appointment; 91% (206) felt comfortable when asked, and 95% (214) found this acceptable. Fifty-one staff responded (36% response rate), 67% (34) female, 55% (28) heterosexual, 35% (18) LGBT. 43% (22) were nurses, 31% (16) doctors, 12% (6) health advisers and 8% (4) healthcare assistants. The majority of staff 96% (49) were confident with conducting routine enquiry, 92% (47) agreed patients found it acceptable; 92% (47) felt routine enquiry was appropriate and 92% (47) had received targeted training. Conclusion: Respondents were overwhelmingly in favour of routine DA enquiry within SHS, and this initiative could be easily adapted in other specialties alongside staff training.